(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to explore how the environment strategies affect improving the dimensions of marketing performance of "Abar Food Company" in Jeddah. It also contributes to clarifying the role of this strategy in leading food trade and industry products and markets. This study targets one of the distinguished companies in the Saudi market that aims to provide high value to customers, and achieve innovation, growth, progress and continuous success. The importance of this study lies in understanding how ocean strategies affect marketing performance enhancement, and providing practical recommendations for the company to improve its strategies and increase its ability to compete in the market, and enhancing our understanding of the role of ocean strategies in enhancing marketing performance and improving the competitiveness of companies in the local market, which contributes to developing business strategies in it and in addition to current research on ocean strategies and their impact on marketing performance, and providing practical recommendations for "Abar Food Company" in Jeddah, especially since Jeddah is a major commercial center characterized by constant movement, as it has developed greatly in all commercial and service fields, and has a major industrial renaissance, which has made it one of the most attractive cities in the world for business and trade, so it has become an important center for money, business and industries. This study relied on the descriptive analytical approach to answer the study questions and test the validity of the hypotheses. It includes collecting data through a joint voice questionnaire for the marketing management of Abar Company and a sample of customers. The study concluded that Abar Company can focus on expanding geographical presence, improving customer satisfaction, increasing profitability, and activating blue ocean strategies in a thoughtful manner. The company should promote innovation with a focus on improving efficiency and expanding sales channels, as well as enhancing organizational culture and using electronic channels to achieve its goals effectively.